A ciência que não vemos: o jornalismo literário como meio de desvelamento de ideologias e polifonia na comunicação pública da ciência - Passos, Mateus Yuri Ribeiro da Silva (Universidade Federal de São Carlos, 2010)
From a diagnosis according to which there is a gap between common people and the research and development institutions, some studies in the public communication of science aim to gather solutions for reducing it a process in which journalism may be a key tool. This paper aims to analyze science reportages published in three magazines Ciência Hoje, Pesquisa Fapesp and piauí that have narrative aspects. Since the press uses many strategies to bring its public closer to science, we assume that the immersion reportage, using literary techniques, may be a way to achieve it. This research explores the narrative and discourse construction in science journalism and how the pieces handle polyphonic discourses, in order to identify literary journalism characteristics, diversity of themes and approaches to science, as well as to select some procedures which science reporters may use in newscovering. Our corpus was analyzed in a qualitative approache according to Bakhtin s discourse theories and the propositions of Science, Technology and Society and public communication of science studies, in order to promote a better interaction between science and other forms of knowledge, and also to bring a constructive view of science.
Keywords: Comunicação; Jornalismo científico; Jornalismo literário; Linguagem; Discurso; Desenvolvimento social - ciência, tecnologia e sociedade; Science, Technology and Society; Public communication of science; science Journalism; Literary Journalism; Discourse and Language; Science in the making; CIENCIAS SOCIAIS APLICADAS